(untitled) - Aziz, Sartaj (Paris, France, 1990)
Contents: Chapter 1. Introduction; Chapter 2. Policies for increasing agricultural production; Chapter 3. Policies for improving food security;... .
Keywords: Nhà nước và nông nghiệp,Agriculture and state; Nước đang phát triển,Developing countries